Dėl baltų kalbų nenominatyvinės praeities - Palmaitis, Letas (Baltistica, 1977)
ON THE NON-NOMINATIVE PAST OF THE BALTIC LANGUAGESThe article enumerates the main works (from 1901 up to 1970) on the non-nominative (ergative) structure of the Indo-European and Baltic parent languages; in the latter the lability of such verbs as virti, sverti, genetivus auctoris and impersonal constructions with object nominative are pointed out to be remnants of its ergativism. Genetivus auctoris shows that an action belongs to its actor and so reflects the archaic Indo-European ergative case from which nominative and genetive have descended. Sentences of visa vagių išvogta type repeat the ergative pattern with vagių as a subject in the „ergative“ case, visa – an object in the „absolute“ case and with predicate išvogta as a seminominal form naming action. Impersonal variants of this pattern may be sentences of the type vãgos išarta and reikia vãgos išarti, the predicate of the latter being an extended predicate of the former: reikia = reikta (impersonal form naming action). A premise for the nominative mounting of the object was the developing of concording of the logical subject with intransitive verb in favour of acc./nom. neutrius as much as in favour of nom. communis in which concording of the logical subject with a transitive verb was developing. This fact weakened the differentiation between acc./nom. neutrius = acc. communis and nom. communis and stimulated the possibility to preserve the sameness of the logical object and the logical subject (the latter earlier connected with intransitive verb) also in the shape of nom. communis. The existence of similar constructions with object nominative in Slavic, Sanskrit, Uralic and Altaic languages is to be explained as coming from the ergative structure of the Boreal (nostratic) super-system. The ergative structure decaying, the homonymy of cases arising in the nominative system in place of the fewer number of former cases brought forth the appearing of synonymous case forms, e.g. I.-E. non-ergat. >nom., non-nom. *-ā = non-nom. *-āi (-i arisen at the same time as in o/e-stems) → nom. *-āi from what have developed Latin nom., dat. -ae, gen. -ae